THE ROLE OF PROVERBS IN WESTERN AND EASTERN LINGUISTIC CULTURE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article is devoted to issues related to determining the similarities and differences of various national English and Uzbek folk proverbs and clarifying their uniqueness and similarity. A detailed study of lexicons in English and Uzbek folk proverbs serves to thoroughly research the specific characteristics of each unit. The author revealed axiological, lexical-semantic features of proverbs with examples.